THE USE OF E-PORTFOLIO TO DEVELOP ENGLISH LANGUAGE LEARNERS' AUTONOMY AND INDEPENDENCE - Oksana I. Ivanova (Інформаційні технології і засоби навчання, 2017)
This paper discusses the findings of a research study concerning the use of e-portfolios to develop learners' autonomy and independence, from the perspectives of teachers and students participating in this study. The findings demonstrate many of the benefits of e-portfolio practice regarding learners’ increased sense of ownership, teacher and peer feedback, enriched learning experience at both individual and technological levels, enhanced opportunity for self-improvement and increased awareness of the learning process. Despite many positive aspects of e-portfolios use, the study reveals some challenges facing students, teachers and support staff, mainly connected with technical problems and Internet access, and the necessity for teachers and learners to change their roles to become more independent in the learning process. The author concludes that e-portfolio is a promising tool to stimulate and challenge students to become independent and self-regulated learners that should be implemented in English language learning at higher educational institutions.